Clean air: an outlook for achieving sustainable development goals: the state of the indoor environment in Michika area of Adamawa state, Nigeria - D. Philemon , Sylvester; Esemuze, Lucky (SPC Journal of Environmental Sciences, 2022)
This study assessed the health implications of air quality decline in residential, workplace, and school indoor environments and its implications on the health of the inhabitants of the Michika Area of Adamawa State. Pollutants such as PM, CO, NO2, and SO2 were evaluated in the morning and evening hours within 10 days using an in situ gas sampler. The data were compared to WHO and NESREA limits for human exposure. Anova and student t-test statistics were adopted to hypothesize the mean differences in the diurnal and spatial conditions of indoor air pollutants. The air quality index was estimated using the US EPA equation to determine the level of indoor air quality in relation to health implications. The study found, among other things, that ambient pollutant concentrations were statistically different in the respective indoor environments for CO (P value = 0.000), SO2 (P values of 0.02 and 0.000), NO2 (P value = 0.000), and PM2.5 (P = 0.001 and 0.0001). The residential indoor environment was reportedly dangerous for sensible groups due to the poor AQI rating for SO2, NO2 and PM10. In conclusion, air pollution is evident in the Michika area of Adamawa State, and the rate of exposure is particularly higher in the residential indoor space.